Gendered and generational tensions in increased land commercialisation: Rural livelihood diversification, changing land use, and food security in Ghana's Brong‐Ahafo region. Issue 1 (29th March 2019) - Mariwah, Simon; Evans, Ruth; Antwi, Kwabena Barima
Abstract : Many smallholder farmers in Jaman North District, Brong‐Ahafo Region, Ghana are shifting from food crop production to increased cultivation of cashew, an export cash crop. This paper examines gendered and generational tensions in increased commercialisation of land, livelihood diversification, and household food security in the context of globalisation and environmental change. Using qualitative, participatory research with 60 middle‐generation men and women, young people and key stakeholders, the research found that community members valued the additional income stream. Young people and women, however, were apprehensive about the long‐term consequences for food security of allocating so much land to cashew plantations. Young, middle, and older generations were concerned about their weak bargaining position in negotiating fair prices with export companies and intermediaries. Greater integration into the global economy exposed rural actors to multiple risks and inequalities, such as the uneven effects of economic globalisation, rises in food prices, hunger and food insecurity, growing competition for land, youth outmigration and climate change. The shift towards cashew cultivation appears to be exacerbating gender and generational inequalities in access to land and food insecurity and leading to exploitation within the global agri‐food supply chain among already vulnerable rural communities in the global South. With stronger farmer associations and cooperatives, however, cashew farmers stand the chance of benefitting from greater integration into the global economy, through strengthened bargaining positions. Greater understanding is needed about the complex interactions between sustainable food systems, changing land use and gender and generational inequalities in rural spaces. Abstract : Increased cashew cultivation has benefits and trade‐offs for small‐holder farmers. However, using communal lands for cashew cultivation can threaten long‐term food security. Therefore, diversification & innovative farming practices may ensure livelihood sustainability. e00073